Preoperative hematocrit levels and postoperative mortality in patients undergoing craniotomy for brain tumors - Xiao, Yangchun; Cheng, Xin; Jia, Lu; Tian, Yixin; He, Jialing; He, Miao; Chen, Lvlin; Hao, Pengfei; Li, Tiangui; Chong, Weelic; Hai, Yang; You, Chao; et al. (Frontiers in Oncology, 2023)
Background: Abnormal hematocrit values, including anemia and polycythemia, are common in patients undergoing craniotomy, but the extent to which preoperative anemia or polycythemia independently increases the risk of mortality is unclear. This retrospective cohort study aimed to examine the association between preoperative anemia and polycythemia and postoperative mortality in patients who underwent craniotomy for brain tumor resection.Methods: We retrospectively analyzed data from 12,170 patients diagnosed with a brain tumor who underwent cranial surgery at West China Hospital between January 2011 and March 2021. The preoperative hematocrit value was defined as the last hematocrit value within 7 days before the operation, and patients were grouped according to the severity of their anemia or polycythemia. We assessed the primary outcome of 30-day postoperative mortality using logistic regression analysis adjusted for potential confounding factors.Results: Multivariable logistic regression analysis reported that the 30-day mortality risk was raised with increasing severity of both anemia and polycythemia. Odds ratios for mild, moderate, and severe anemia were 1.12(95% CI 0.79-1.60), 1.66(95% CI 1.06-2.58), and 2.24(95% CI 0.99-5.06), respectively. Odds ratios for mild, moderate, and severe polycythemia were 1.40(95% CI 0.95-2.07), 2.81(95% CI 1.32-5.99), and 14.32(95% CI 3.84-53.44), respectively.Conclusions: This study demonstrated that moderate to severe anemia and polycythemia are independently associated with increased postoperative mortality in patients undergoing craniotomy for brain tumor resection.These findings underscore the importance of identifying and managing abnormal hematocrit values before craniotomy surgery.